ASSESSMENT OF GENETIC VARIABILITY AMONG SELECTED SPECIES OF APOCYNACEAE ON THE BASIS OF rps 11 GENE - M. Ibrahim; N. Nazar; M. Ilyas; T. Mahmood (Journal of Animal and Plant Sciences, 2014)
The importance of genetic variation for sustaining biological diversity and evolutionary processes is widely accepted. The present study aims to investigate the phylogenetic relationships among five selected species of Apocynaceae collected from various regions of Pakistan using chloroplast gene (rps11) which encode ribosomal protein of smaller subunit11. For this purpose rps11 gene was amplified, purified, sequenced from each species and analyzed with MEGA5. Phylogenetic analysis revealed an overall narrow genetic background (0.5 %) among selected species. Nerium oleander, Rhazya stricta and Vinca major were the most similar with a bootstrap value of 24-44 % while Catharanthus roseus and Nerium oleander showed distant relationship. Divergence value was observed within a range of 0.023-9.994 on the basis of pair wise distance calculation. The study further confirmed the use of rps11 gene as a potential candidate for phylogenetic analysis.
Keywords: Apocynaceae; rps11; Genetic Variation